Prevalence of dental fluorosis in Bauru, São Paulo, Brazil - Ramires, Irene; Pessan, Juliano Pelim [UNESP]; Levy, Flávia Mauad; Rodrigues, Maria Heloísa Correia; De Almeida, Beatriz Simões; Kato, Melissa Thiemi; Sales Peres, Silvia Helena de Carvalho; Buzalaf, Marília Afonso Rabelo (FapUNIFESP (SciELO), 2007)
Objective: To evaluate the prevalence of dental fluorosis in scholars aging 12 to 15 years old, residents in the city of Bauru, State of São Paulo, Brazil. Methods: 1318 volunteers were enrolled in this study and examined in 18 public schools of the State of São Paulo. The examinations were performed in the schools' court by three dentists (with a Master's degree in Public Health), after toothbrushing supervised by another dentist. The teeth were dried with cotton pellets and examined under natural light by visual inspection, using an explorer as recommended by the WHO, a plane mirror and a tongue depressor. The Thylstrup-Fejerskov (TF) index was used for rating fluorosis. Intra and inter-examiner reproducibility was calculated and data were submitted to descriptive analysis. Results: Approximately 36% of the children presented dental fluorosis, of which 28% was diagnosed as TF1 while the remaining received scores between TF2 and TF4. Conclusion: The prevalence of dental fluorosis in Bauru is within the expected range, based on previous studies. Although fluoride is an important resource for caries control, its use must be adequate to the needs of each specific population.
Keywords: Dental fluorosis; Epidemiology; Fluoride